The Influence of Meaningful Work on Work Engagement among Employees of the Regional Office of Ministry X, West Sumatra - Azizah Meihana; Suci Rahma Nio (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Low levels of work engagement in the government sector may reduce the quality of public services, making it important to identify factors that can strengthen employee engagement. Meaningful work is one factor assumed to influence work engagement. This study aims to determine the effect of meaningful work on work engagement among employees of the Regional Office of Ministry X in West Sumatra Province. A quantitative causal approach was employed using simple linear regression analysis. The sample consisted of 106 employees selected through probability sampling. Data were collected using the Work and Meaning Inventory (WAMI) and the Utrecht Work Engagement Scale (UWES). The findings indicate that meaningful work has a significant effect on work engagement (p < .05), with a regression coefficient of 0.817. The R value of 0.455 indicates a moderate relationship, while the R² value of 0.207 shows that meaningful work contributes 20.7% to work engagement. These findings suggest that higher levels of meaningful work are associated with higher levels of employee work engagement. This study contributes to the literature on organizational behavior in the public sector by providing empirical evidence of the role of meaningful work in strengthening work engagement. Practically, the findings imply that bureaucratic institutions should strengthen employees’ sense of meaning in their work to enhance engagement and support the improvement of public service quality.